Resolva a equação: 3 (2x-1) = - 2 (x+3)
Soluções para a tarefa
Respondido por
0
Resposta:
x=-3/8
Explicação passo-a-passo:
3.(2x-1) = - 2.(x+3)
6x-3=-2x-6
6x+2x=-6+3
8x=-3
x=-3/8
Respondido por
2
Resposta:
3(2x - 1) = -2(x + 3)
6x - 3 = -2x - 6
6x + 2x = -6 + 3
8x = -3
x = -3/8
Resposta: x = -3/8
Explicação passo-a-passo:
eai ajudou ?
Perguntas interessantes
Matemática,
10 meses atrás
Geografia,
10 meses atrás
Biologia,
10 meses atrás
Português,
1 ano atrás
Física,
1 ano atrás
Ed. Física,
1 ano atrás